The Late Promoter of the Human Cytomegalovirus Viral DNA Polymerase Processivity Factor Has an Impact on Delayed Early and Late Viral Gene Products but Not on Viral DNA Synthesis - Isomura, Hiroki (American Society for Microbiology (ASM), 2007)
Transcription of the DNA polymerase processivity factor gene (UL44) of human cytomegalovirus initiates at three distinct start sites, which are differentially regulated during productive infection. Two of these start sites, the distal and proximal sites, are active at early times, and the middle start site is active at only late times after infection (F. Leach and E. S. Mocarski, J. Virol. 63:1783-1791, 1989). Compared to the wild type, UL44 gene expression was lower for recombinant viruses with the distal or the middle TATA element mutated. The transcripts initiating from the distal or middle start site facilitated late viral gene expression. The level of viral DNA synthesis was affected by mutation of the distal TATA element. In contrast, mutation of the middle TATA element did not affect the level of viral DNA synthesis, but it did affect significantly the level of late viral gene expression. Recombinant viruses with the distal or middle TATA element mutated grew more slowly than the wild type at both low and high multiplicities of infection. Reduced expression of the UL44 gene from the late middle viral promoter correlated with decreased late viral protein expression and decreased viral growth.